Estudio interdisciplinar sobre modelos matemáticos de similitud aplicados a la música popular colombiana (Cuadernos de Análisis y Debate sobre Músicas Latinoamericanas Contemporáneas, 2022)
Currently, multidisciplinary research extends with greater impact to musical studies. Since it allows observations from different angles of pre-established theoretical concepts or the deepening of them based on the procedures and methodologies used in other disciplines. It is for the aforementioned that in this consolidated some mathematical processes are implemented that allow calculating the distances between musical genres based on the comparison of their results, which intend to trace. In future investigations their possible genealogical origin through the interpretation of their data.
Keywords: multidisciplinary; musical genres; mathematical measurement models; data interpretation; mathematization; rhythmic structure; genealogy